(untitled) (Global Scientific Review, 2026)
This paper investigates the root causes of corrosion in reinforced concrete (RC) structures, advanced methods for protecting reinforcing steel from rusting, and technologies aimed at increasing concrete density and impermeability. The study analyzes electrochemical corrosion mechanisms and the degradation of concrete microstructure under aggressive environmental exposure, including carbonation and chloride ingress. Furthermore, the effectiveness of next-generation corrosionresistant chemical additives (inhibitors), hydrophobic surface systems, and composite reinforcement alternatives is comparatively evaluated. A multi-level durability strategy is proposed, combining material design, structural detailing, protective systems, and monitoring. The results provide practical recommendations for extending the service life of buildings and infrastructure in aggressive environments, including regions with high groundwater salinity and cyclic wetting-drying conditions.